Faktor-Faktor yang Mempengaruhi Kinerja Karyawan Pada Universitas Internasional Semen Indonesia (UISI) - Moh. Naufal Fanani; Mirza Dwinanda Ilmawan; Aditya Narendra Wardhana (Jurnal Manajerial, 2020)
Background/ Purpose - To find out what factors influence employee performance at Semen Indonesia International University (UISI). Design / Methodology / Approach - This research is quantitative research. The sample in this study were UISI employees and lecturers who had structural positions at UISI where only lecturers were not used as respondents. The sampling technique uses simple random sampling and obtained a sample of 79 respondents. The data analysis of this study used multiple linear regression analysis using the assistance of the IBM SPSS Statistics 23 program as if the statistical data. Results and Discussion - The results of this study found that instrument testing, classic assumption tests, t tests, coefficient of determination (R2) and multiple linear regression analysis on the compensation variable hypothesis, work environment, organizational culture, leadership, motivation and job satisfaction showed no significant influence on employee performance so the hypothesis is rejected. While the variable work discipline shows a significant effect on employee performance. Conclusion - Based on the results of the study prove that all hypotheses are acceptable (compensation, work environment, organizational culture, leadership, motivation and job satisfaction have no significant effect on employee performance. While work discipline variables have a significant effect on employee performance). Research Implications - It is expected that the results of this study can add insight related to improving employee performance to pay attention to aspects of work discipline.